Biportal Endoscopic Intervention for Lumbar Disk Herniation: Evaluating Clinical Effectiveness and Patient Outcomes - Apoorv Kumar; Arohi Gupta; Sujith V Rao; Huzaifa A Ansari (Journal of Orthopedics and Joint Surgery)
Aims and background: Lumbar disk herniation (LDH) affects millions worldwide, spurring advancements in treatment. Biportal endoscopic spinal surgery (BESS) emerges as a promising approach, minimizing invasiveness. BESS employs specialized tools using two stab incisions. This study assesses BESS efficacy in treating LDH, analyzing surgical outcomes and potential complications from existing literature. Methods: A thorough literature review evaluated BESS efficacy in LDH management. Multiple databases were queried for studies on BESS outcomes and complications. Inclusion criteria comprised studies assessing postoperative results using clinical scores like visual analog scale, MacNab criteria, and Oswestry disability index. Data synthesis provided insights into BESS effectiveness and limitations. Results: The review reveals favorable postoperative outcomes with BESS, reflected in clinical scoring systems. Common benefits include pain reduction, enhanced function, and high patient satisfaction. In contrast to traditional open surgery, BESS offers advantages such as diminished blood loss and abbreviated hospital stays, alongside quicker recovery times. However, challenges, including a learning curve for surgeons and practical obstacles, still exist. Conclusion: BESS presents promise for LDH management with favorable postoperative outcomes and benefits over traditional methods. Acknowledging challenges, it calls for careful integration into clinical practice and ongoing research to refine techniques, with the aim to improve surgical outcomes and elevate the quality of life of our patients. Clinical significance: This study underscores BESS as a valuable LDH treatment option, especially in specific patient groups. It offers insights to aid clinicians in informed decision-making, emphasizing the need for ongoing surgical advancements to enhance BESS efficacy and safety, thereby improving patient care.